DAMPAK INOVASI TEKNOLOGI INFORMASI DAN KOMUNIKASI TERHADAP PENDIDIKAN DI MASA PANDEMI COVID 19 - Nur Afni; Hairuddin Cikka; Iksan Kahar (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2021)
The Covid-19 pandemic has hit many countries around the world. Almost all activities have been limited with the aim of preventing the corona virus from spreading, one of which has felt the impact is educational activities. Since 2019 until today, Indonesia has carried out an online learning process. With online learning, it opens our thinking horizons for the enormous potential of information and communication technology (internet) which previously was not used optimally in various lines of life, especially in the field of education, without being limited by space and time, educational activities can be carried out anywhere and anytime. In addition, while there is no certainty when this pandemic will end, strong learning is an absolute necessity that must be met by all Indonesian people.